ANALISIS PELAKSANAAN PEMBELAJARAN ONLINE PADA SISWA SMA DALAM MASA PANDEMIK COVID-19 - Nova Irawati Simatupang; Ismenny Martalena Simatupang; Angel Patricia Situmorang; Sri Rejeki Ignasia Sitohang (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
Covid-19 pandemic causes very significant changes by making physical and social distancing regulations. Changes occur mainly in the field of education which makes the learning system in schools implement online learning. Through this research, researchers conducted an analysis of the implementation of online learning of high school students during the co-19 pandemic period. The purpose of this research is to find out how the implementation of online learning during the co-19 pandemic period. Te research was conducted using a questionnaire online. Based on the data it was found that 50% of respondents stated that they had never used online learning media before the enactment of online learning, 78% implementation of online learning was carried out according to school schedules, 28% of students could understand when taught online, 25% giving feedback when starting lessons (pre test) and end (post test), 78% of students take online learning, 81% of learning activities are carried out using video/youtube/ percentage recording, 78% use of smartphone as a medium used to access learning and online learning platforms that the most widely used during this pandemic is classroom, which was chosen by 38% of respondents. In situation like this, online learning can be done to the maximum if the teacher and students want to adapt the changes and developments in IT.